ASSOCIATION BETWEEN LINEAR TRAITS OF LEGS AND LONGEVITY OF UKRAINIAN BROWN DAIRY COWS - V. I. Ladyka; L. M. Khmelnychyi; S. L. Khmelnychyi; A. M. Salohub; V. V. Vechorka (Journal of Animal and Plant Sciences, 2020)
The influence of conformation traits that characterize mobility, on the life expectancy of Ukrainian brown dairy cows was investigated: rear legs side view (RLS), rear legs rear view (RLRV), hooves angle (FA), and locomotion (L). The dataset consisted of records about productive and linear traits of 489 cows collected from January 1, 2006 to December 31, 2016. Cows with 1-4 scores for RLS were at higher risk of culling than animals with legs close together estimated at 6-9 scores. Cows with optimal development of the trait were used in the herd much longer compared to groups of animals with an estimate of 1-4 scores on 126-831 days and with estimate of 7-9 scores – on 286-505 days. Cows with the highest classification score of the RLRV were lived on 605 days longer compared to animals with 1 score. The dependence of cows longevity on the condition of FA was evidenced by a significant difference between groups of cows with estimates in 7 and 3 scores, which amounted 312 days. Cows with 9 scores for locomotion (L) were retained for 777 days longer as compared to animals with 1 score. The influence of linear traits characterizing extremities development on the life expectancy of cows of Ukrainian brown dairy cattle can be a predictor of longevity that allows indirect cow selection by type.
Keywords: Ukrainian Brown Dairy; Longevity; Linear Type Traits; Survival Analysis